Some Aspects of Bio-ecology of Walking Shark (Hemiscyllium galei) in Doreri Bay, Manokwari, Indonesia - Muhammad Fadil Insani; Ridwan Sala; Duaitd Kolibongso (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Walking sharks are endemic to the New Guinea-Australian region, inhabiting shallow reef ecosystems. In Papuan waters there are four species of walking sharks, including Hemiscyllium galei. This research investigated ecological and biological aspects of H. galei in Doreri Bay near Manokwari, West Papua Province. The samples used in this study were collected from two locations in the waters of Doreri Bay, namely the islands of Arowi and Nusmapi between September and November 2020. This research was conducted using underwater visual census (UVC) during nighttime. Observations were made at two locations covering a total area 9,000 m2. A total of 10 individuals (7 males and 3 females) of H. galei were collected during the study. They were identified as distinct individuals based on spot shapes on the pectorals. All of them were then measured their morphometric parameters including total length, precaudal-fin length, head length, and body weight. After measurements were taken, all individual sharks were safely released back into their habitat. Morphometric measurements showed the total length of individual walking sharks obtained was no more than 75 cm for both male and female individuals. The abundance estimates of H. galei at Arowi and Nusmapi were 13,33 ind.ha-1 and 8,88 ind.ha-1 respectively. Analysis of length-weight relationship showed a negative allometric growth pattern, where body length growth was faster than weight gain.  Based on the present study, walking sharks probably occupies only a limited area in Doreri Bay, and are therefore very vulnerable to the daily activities of humans living in the vicinity.